2021
DOI: 10.1093/ntr/ntab226
|View full text |Cite
|
Sign up to set email alerts
|

Examining Truth and State-Sponsored Media Campaigns as a Means of Decreasing Youth Smoking and Related Disparities in the United States

Abstract: Introduction To analyze the impact of Truth and state-sponsored anti-tobacco media campaigns on youth smoking in the U.S., and their potential to reduce tobacco-related health disparities. Methods Our study included data from the 2000-2015 Monitoring the Future study, an annual nationally representative survey of youth in 8 th (n=201,913), 10 th (n=194,468), and 12 th grades (n=178,379). Our primary exposure was Gross Ratings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…A recent study indicated the likelihood of youth recalling a YouTube antismoking message doubled with each completed ad view, but not with the number of ads served, with around three-quarters of the skippable videos served skipped. 41 Other priority questions include: are some people, including audiences campaigns most want to reach, more likely to skip than others? ; which kinds of messages are more likely to be skipped?…”
Section: Campaign Reachmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent study indicated the likelihood of youth recalling a YouTube antismoking message doubled with each completed ad view, but not with the number of ads served, with around three-quarters of the skippable videos served skipped. 41 Other priority questions include: are some people, including audiences campaigns most want to reach, more likely to skip than others? ; which kinds of messages are more likely to be skipped?…”
Section: Campaign Reachmentioning
confidence: 99%
“…48 49 There is also evidence that greater levels of exposure to youth antitobacco campaigns has been associated with more pronounced effects on lowering smoking rates among 10th and 12th graders from lower compared with higher socioeconomic backgrounds. 41 Given the tobacco industry's targeting of Indigenous, black, LGBT and other ethnic minority communities, 50 achieving antitobacco campaign reach that exceeds that of other lower prevalence communities is particularly important. Allen and colleagues' 5 review urges that 'the media purchase should ensure exposure among racial/ethnic minority populations' and suggests it is important to '…supplement national media… through channels that reach a large proportion of at-risk minority individuals'.…”
Section: Special Communicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Elements such as availability, level of exposure to social media in targeted geographical region, appointing effective communication channels, presenting appropriate slogans or messages or visualized contents such as pictures or videos, also having a regular schedule, the determination of a target community and considering the educational level, age and gender of audiences [220][221][222][223] play critical role in a fruitful viral hepatitis campaign. In addition, one of the most important elements in campaigns is the choice of an appropriate message (warning, fear, excitement and pleasure) in line with the campaign goals.…”
Section: Merging Strategiesmentioning
confidence: 99%